2017
DOI: 10.1155/2017/3702605
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Critically Ill Patients with Testicular Cancer

Abstract: Purpose To evaluate the clinical characteristics and outcomes of critically ill patients with testicular cancer (TC) admitted to an oncological intensive care unit (ICU). Methods This was a prospective observational study. There were no interventions. Results During the study period, 1,402 patients with TC were admitted to the Department of Oncology, and 60 patients (4.3%) were admitted to the ICU. The most common histologic type was nonseminomatous germ cell tumors (55/91.7%). The ICU, hospital, and 6-month m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Figures 4 and 5 (http://links.lww.com/CCX/B54) show the pooled hospital mortality rates for patients with hematologic and solid malignancies. Seven studies reported data enabling direct comparison of these subgroups (4, 14, 21, 26, 42, 50, 55). Patients with hematologic malignancies were 43% more likely to die in the hospital than were patients with solid malignancies (RR, 1.43; 95% CI, 1.13–1.81; I 2 = 96.3%) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the presence of elevated total bilirubin level was associated with both ICU and hospital mortality. Ñamendys-Silva et al [ 14 ] also reported that total bilirubin level is one of the predictors for organ failure that is associated with ICU mortality. On the other hand, Regazzoni et al [ 19 ] did not find a significant association between liver dysfunction and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…17 Patients may present with a testicular mass and can develop additional symptoms from growing metastatic lesions, but the prognosis is generally good — with 5-year survival rates of 97% — because most cases are caught early. 17 – 20 …”
mentioning
confidence: 99%
“… 18 , 19 Patients with TGCTs are nearly always seen and treated by an oncologist, because cure and long-term survival are possible, even if they are more challenging with advanced presentations. 19 , 20 Based on their histology, TGCTs are classified as seminomas or nonseminomas and given a stage of I to III. Stage I disease typically requires orchiectomy alone; stage II disease requires further surgery, radiation (for seminomas) or systemic therapy (for lymph nodes); and stage III disease requires systemic therapy for metastatic disease.…”
mentioning
confidence: 99%